Deterioration model for the assessment of longan senescence and decay - Sommano S. (2014)
The correlation of browning index (BI) to decay parameters was determined using total soluble solid content (TSS), ethanol and ethanol/TSS ratio. Longan fruits were harvested traditionally and compared with precooling technique. It was found that longan fruit, harvested without cooling, exhibited better colour retention, and less off-flavour production. All parameters except TSS gave a good correlation with storage time. The relations of BI to ethanol and ethanol/TSS were also observed and high regression coefficients were also found (R2>0.80). The data all fitted well with linear regressions, thus giving the model to predict storage time of the longan fruit after harvest as: (D=2.14x-0.6, R2= 0.75) where x = BI×(E/T).